Open Science: Reinventing the Librarianship - Keskitalo, Esa-Pekka; Vienonen, Tanja (Septentrio Conference Series, 2016)
Better utilisation of publicly funded research output is an aim of the Finnish Government. To reach that aim, the Open Science and Research (ATT) Initiative was launched in 2014. Lead by the Ministry of Education and Culture, the ATT Initiative has funded a number of projects that support good research data management, opening of research data, and Open Access in general. The Initiative also emphasises cooperation and interoperability nationally, and internationally. The National Library of Finland and other research libraries have an important role in the ATT Initiative. Libraries are in a good position to make meaningful contributions as they can repurpose their expertise on metadata, information retrieval, and collection management. They are finding new ways of collaboration and creating services in the fields of Open Access and Open Science. Libraries and other service providers should, first and foremost, respect the needs of research and researchers: science should always be the guiding force. But Open Access and Open Science do have an effect on how research is conducted and published. Therefore, it must be possible to have a critical look on conventional research practices. Increasing amounts of data, new technological possibilities, and new methods of analysis mean that old practices need to be revised. The more pronounced demands of interoperability and innovative re-usability drive for change, too. Of course, the funders are also very keen on cost-efficiency and measurable impact. There is a demand for harmonisation, collaboration, and shared infrastructures and services. The Open Scientific Publishing Project (TAJUA) in the National Library of Finland is a part of the ATT Initiative. The main focus of the project is to increase and improve the availability of Finnish research output. It comprises of several subprojects that build on the existing expertise of the Library, taking it to new directions. They deal with improving the institutional repository infrastructure provided by the National Library, with special attention to organisations with restricted resources and basic demands; better guidance for institutional repositories on best practices in metadata creation, licensing, and in gathering statistics in a commensurable manner; a tool for easy creation of metadata about research datasets; improved persistent identifier services (ISNI, ORCID, URN, etc.); better understanding of economics of Open Access publishing, e.g. real level of APC, and recommendations for changes in publishing workflows; and recommendations for ensuring long-term accessibility of scientific output. The TAJUA project complements others under the umbrella of the ATT Initiative. They deal with more efficient publishing workflows, data management planning, opening datasets, training and education on Open Science, and tools to enrich and work up open linked data. Existing national services on data storage, preservation, and dissemination will also be extended. Research libraries should not be shy about their knowledge and skills. With metadata being the new black, they can really make their mark on the world of Open Science.